A finishing process via ultrasonic drilling for additively manufactured carbon fiber composites. Issue 4 (5th May 2021) - Parandoush, Pedram; Fernando, Palamandadige; Zhang, Hao; Ye, Chang; Xiao, Junfeng; Zhang, Meng; Lin, Dong
Abstract : Purpose: Additively manufactured objects have layered structures, which means post processing is often required to achieve a desired surface finish. Furthermore, the additive nature of the process makes it less accurate than subtractive processes. Hence, additive manufacturing techniques could tremendously benefit from finishing processes to improve their geometric tolerance and surface finish. Design/methodology/approach: Rotary ultrasonic machining (RUM) was chosen as a finishing operation for drilling additively manufactured carbon fiber reinforced polymer (CFRP) composites. Two distinct additive manufacturing methods of fused deposition modeling (FDM) and laser-assisted laminated object manufacturing (LA-LOM) were used to fabricate CFRP plates with continuous carbon fiber reinforcement. The influence of the feedrate, tool rotation speed and ultrasonic power of the RUM process parameters on the aforementioned quality characteristics revealed the feasibility of RUM process as a finishing operation for additive manufactured CFRP. Findings: The quality of drilled holes in the CFRP plates fabricated via LA-LOM was supremely superior to the FDM counterparts with less pullout delamination, smoother surface and less burr formation. The strong interfacial bonding in LA-LOM proven to be superior to FDM was able to endure higher cutting force of the RUM process. The cutting force and cutting temperature overwhelmed the FDM parts and induced higher surface damage. Originality/value: Overall, the present study demonstrates the feasibility of a hybrid additive and subtractive manufacturing method that could potentially reduce cost and waste of the CFRP production for industrial applications.